Теорії міфу та ритуалу в дослідженнях Дж. Фрейзера - Шадріна, Тетяна Володимирівна; Shadrina, T. V. (My University, 2014)
У статті проаналізовано дослідження Дж. Фрейзера, викладених у його фундаментальній праці “Золота гілка”. Дж. Фрейзер – один із засновників антропологічної школи, міфологічні теорії якої стали своєрідним підґрунтям для формування міфокритичної методології ХХ ст. The article deals with the creative work of J.G. Fraser – the anthropologist of the 19th century, who was one of the founders of the anthropological school. We analyze the key points of J.G. Fraser’s critical work “The Golden Bough”, which gave way to the whole myth method. J.G. Fraser develops the ideas of E. Tylor (“theory of animism”, “theory of survivals”) and A. Lang (myth is a primitive science). According to the Fraser’s work myth is a primitive science which throws light on the culture and numerous modern facts and things. Myth is connected with ritual and illustrates it. The particular attention is at the King’s Ritual in a lot of ancient tribes which represents the death of the king, his leave and rebirth and at last – return. The stages of the king-god’s existing resemble yearly dying off and rebirth of the nature. J.G. Fraser explores evolution of the consciousness of people from magic through religion and to science. He considers the next stage is timely when the previous one is outdated and the mind of the society is mature enough to step to the new stage. Taboo is taken as primitive laws of barbarian jurisdiction. The traces of modern tradition and moral laws can be found in these survivals – taboo. The majority of Fraser’s theories were used not only by Cambridge school (the 20th c.) – who followed the anthropological ideas of the 19th century and created myth method in the literary criticism, but also by their opponents – the founders of the archetypal criticism.
Theories of Myth and Ritual in the Research Work of J. Fraser
Keywords: міф; ритуал; магія; релігія; наука; антропологічна школа; теорія пережитків; анімізм; тотемізм; табу; цап відбувайло; міфологія; myth; ritual; magic; religion; science; the anthropological school; theory of survivals; animism; totemism; taboo; scapegoat; mythology